2021
DOI: 10.1097/mnm.0000000000001523
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics model based on preoperative 18F-fluorodeoxyglucose PET predicts N2-3b lymph node metastasis in gastric cancer patients

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Xue et al ( 66 , 72 ) published two more studies in 2022 and 2023, respectively. In the first study, the authors enrolled 127 patients with pathologically confirmed GC who underwent preoperative 18F-fluorodeoxyglucose (18F-FDG) PET/CT, with the aim of building and validating an 18F-FDG PET-based radiomics nomogram to predict N2-3b LNM.…”
Section: Resultsmentioning
confidence: 99%
“…Xue et al ( 66 , 72 ) published two more studies in 2022 and 2023, respectively. In the first study, the authors enrolled 127 patients with pathologically confirmed GC who underwent preoperative 18F-fluorodeoxyglucose (18F-FDG) PET/CT, with the aim of building and validating an 18F-FDG PET-based radiomics nomogram to predict N2-3b LNM.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 studies on gastric cancer were found [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], all using 18F-FDG as radiopharmaceutical. The average number of patients included was 163.7 (range 79–214), with 5/7 (71.4%) studies including more than 100 patients, 5/7 (71.4%) using a separate validation dataset and 1/7 (14.3%) using prospective data.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 4 studies were conducted for diagnostic purposes: 2 for nodal involvement prediction (AUC between 0.74 and 0.81) [ 29 , 35 ], 1 for peritoneal involvement prediction (AUC 0.88 in the validation cohorts) [ 30 ] and 1 to differentiate between gastric cancer and primary gastric lymphoma (AUC 0.77) [ 31 ]. The remaining three were prognosis-oriented [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, regional lymph node metastasis of gastric cancer showed significant correlations with PET/CT textural features, demonstrating high intra-tumoral metabolic heterogeneity in gastric cancer lesions with lymph node metastasis. Therefore, in addition to conventional PET/CT parameters, textural features of AGC might have predictive value for histopathological features and lymph node metastasis in patients with AGC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%